Antifungal response of or-al-associated candidal reference strains (American Type Culture Collection) by supercritical fluid extract of nutmeg seeds for geriatric denture wearers: An in vitro screening study - Meenakshi Iyer; Anil Kumar Gujjari; Vishakante Gowda; Shridhar Angadi (Wolters Kluwer Medknow Publications, 2017)
Objectives: Since time immemorial, plants have continued to play a predominant role in the maintenance of human health as sources of medicinal compounds. Several effective antifungal agents are available for oral Candida infections; the failure is not uncommon because isolates of Candida albicans may exhibit resistance to the drug during therapy. The present study aimed to identify an alternative, inexpensive, simple, and effective method of preventing and controlling the candidal infection. Methodology: All the procured and authenticated nutmeg seeds were dried in shade and cleaned by hand sorting. The crushed seeds were passed through mesh no. 40 individually. About 50 g of powdered nutmeg seeds was loaded in the supercritical fluid extractor unit using supercritical CO2 as extracting solvent in accordance with the methods of Nguyen et al. Supercritical fluid (SFE) extraction was done using CO2 gas without any cosolvents. Results: The nutmeg extract displayed antifungal activity with the effective zone of inhibition ranging from 18.0 to 12.0 mm when compared with nystatin as positive control. Conclusion: This paper described the in vitro antibacterial activity, and phytochemical analysis of SFE extract of nutmeg (Myristica fragrans) evaluated against C. albicans (American Type Culture Collection 10231) through agar well diffusion method. SFE of nutmeg seeds can be used as an adjunct to conventional therapy for oral candidiasis.